Big Data Analytics : A Social Network Approach - Panda, Mrutyunjaya; Abraham, Ajith; Hassanien, Aboul Ella; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
Social networking has increased drastically in recent years, resulting in an increased amount of data being created daily. Furthermore, diversity of issues and complexity of the social networks pose a challenge in social network mining. Traditional algorithm software cannot deal with such complex and vast amounts of data, necessitating the development of novel analytic approaches and tools. This reference work deals with social network aspects ofbig data analytics. It covers theory, practices and challenges in social networking. The book spans numerous disciplines like neural networking, deep learning, artificial intelligence, visualization, e-learning in higher education, e-healthcare, security and intrusion detection.
Linkage based Social Network Analysis in Distributed Platform -- Ranjan Kumar Behera, Monalisa Jena, Debadatta Naik, Bibudatta Sahoo, and Santanu Kumar Rath -- An Analysis of AI based Supervised Classifiers for Intrusion Detection in Big Data -- Gulshan Kumar, and Kutub Thakur -- Big Data Techniques in Social Network Analysis -- B.K. Tripathy, Sooraj T.R., and RK Mohanty -- Analysis of Deep Learning Tools and Applications in e-Healthcare -- Rojalina Priyadarshini, Rabindra K. Barik, Brojo Kishore Mishra, Harishchandra Dubey, and Kunal Mankodiya -- Assessing the Effectiveness of IPTEACES e-Learning Framework in Higher Education: An Australians Perspective -- Tomayess Issa, Nuno Pena, and Pedro Isaias -- Review Study: CAPTCHA Mechanisms for Protecting Web services against Automated Bots Mohamed Torky and Aboul Ella Hassanien -- Colored Petri Net Model for Blocking Misleading Information Propagation in Online Social Networks -- Mohamed Torky and Aboul Ella Hassanien -- The Conceptual and Architectural Design of Genetic-Based Optimal Pattern Warehousing System -- Vishakha Agarwal, Akhilesh Tiwari, R. K. Gupta, and Uday Pratap Singh -- Controlling Social Information Cascade: A Survey -- Ragia Ibrahim, Aboul Ella Hassanien Ali. and Hesham Hefniy -- Swarms optimization for Community Detection in Complex Networks: A Comparative Analysis -- Khaled Ahmed, Ramadan Babers, Ashraf Darwish and Aboul Ella Hassanien Ali -- Trustworthiness in the Social Internet of Things -- B. K. Tripathy and Deboleena Dutta -- Big Data Analysis: Technology and Applications -- Abhijit Suprem -- Social Networking in Higher Education: Saudi Arabia perspective -- Khalid Almufaraj and Tomayess Issa -- Animal Social Networks Analysis: Reviews, Tools and Challenges -- Ashraf Darwish, and Aboul ella Hassanien.
Includes bibliographical references and index.
Also available in print format.
Keywords: COMPUTERS / Database Management / Data Mining; COMPUTERS / Internet / General; big data analytics; distributed data mining; hadoop; machine learning; predictive analytics; real time analytics; Big data; Discourse analysis, Narrative; Truthfulness and falsehood; Online social networks; Electronic books